Pemetaan Potensi Bencana dan Sumberdaya Pendukung Program Kampung Siaga Bencana Kalurahan Condongcatur - Beti Kartiningrum; Rijel Samaloisa (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The geographical and geological location of Indonesia is very vulnerable to the threat of various types of natural disasters such as earthquakes, tsunamis, volcanic eruptions, landslides, floods, droughts, disease outbreaks and other social disasters. Condongcatur Village, Sleman Regency, Yogyakarta Special Region responded to the existing conditions by forming a Disaster Preparedness Village (KSB) on October 20, 2022. This research was conducted to describe the disaster potential and potential resources supporting the existence of a disaster preparedness village in the Condongcatur Sub-district and to find out the response of the Condongcatur community in facing disasters. This research uses mixed methods. The object of this research is the disaster potential in the Condongcatur sub-district area, the potential supporting resources of KSB and the community's response and the subjects in this research are the Head of Condongcatur KSB, Condongcatur KSB Team and Condongcatur community. Data collection methods were conducted through interviews and observations with the selection of informants in accordance with the objectives of this study. The geographical and geological location of Indonesia is very vulnerable to the threat of various types of natural disasters such as earthquakes, tsunamis, volcanic eruptions, landslides, floods, droughts, disease outbreaks and other social disasters. Condongcatur Village, Sleman Regency, Yogyakarta Special Region responded to the existing conditions by forming a Disaster Preparedness Village (KSB) on October 20, 2022. This research was conducted to describe the disaster potential and potential resources supporting the existence of a disaster preparedness village in the Condongcatur Sub-district and to find out the response of the Condongcatur community in facing disasters. This research uses mixed methods. The object of this research is the disaster potential in the Condongcatur sub-district area, the potential supporting resources of KSB and the community's response and the subjects in this research are the Head of Condongcatur KSB, Condongcatur KSB Team and Condongcatur community. Data collection methods were conducted through interviews and observations with the selection of informants in accordance with the objectives of this study.